Study of PKLMalioboro Relocation Policy on Tourists' Buying Interest to Increase Local Income in the Special Region of Yogyakarta during the Covid-19 Pandemic Era - Manggar Wulan Kusuma; Shita Lusi Wardhani (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
The decrease in the number of tourists in DIY Province, especially the Malioboro area, which occurred during the Covid-19 pandemic, resulted in reduced local revenues for the DIY provincial government. This is due to the enactment of PP Number21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in Indonesia. This condition makes the level of fear of tourists entering the tourist area very high. One of them is the Tourist Area of Malioboro. The very limited location of the PKL is the cause of the emergence of tourist crowds in the Malioboro area. To overcome this, the DIY Provincial Government then made a policy of relocating the Malioboro PKL. With the new location, it is hoped that PKL will further restore the store atmosphere as it was felt by tourists before the Covid-19 pandemic era. Tourists will again feel safe and comfortable visiting the Malioboro PKL. This condition is expected to increase the number of tourists at the Malioboro PKL again so that it can increase the DIY Provincial Pad which had experienced a decline during the Covid-19 pandemic. This study used a survey method with the sample being DIY travelers. The data in this study were processed using SmartPLS 3.0 software. The results of this study show that the store atmosphere variable does not affect the buying interest of tourists. Meanwhile, location variables and experiential marketing positively affect tourists' buying interest. This proves that the increase in PAD, of which occurred due to an increase in the number of tourists visiting DIY after the PPKM policy was relaxed. The increase in PAD was also coupled with an increase in sales of souvenir products typical of Yogyakarta, one of which tourists could get at the Malioboro PKL relocation location.